DETAILED ANALYSIS OF THE PHYSICOCHEMICAL CHARACTERISTICS OF DISTILLATE FRACTIONS - Khurmamatov, Abdugafor; Boyturayev, Sarvar; Shomansurov, Foziljon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This paper presents a comprehensive analysis of the physicochemical properties of distillate fractions obtained during the rectification of a mixture of oil and gas condensate (30% oil and 70% gas condensate). The study was conducted with the aim of optimizing hydrocarbon feedstock processing, considering temperature ranges (20–200°C) and pressure (1–5 atm). Experimental data showed a significant impact of rectification conditions on the composition and quality of the resulting fractions. In particular, the use of packed-valve and valve columns achieved up to 75% yield of gasoline fractions and 15% heavy distillates with higher boiling points. The study also included a comparative analysis of the infrared spectra of two samples of the oil and gas condensate mixture. The first sample was characterized by peaks at 1606.7 cm⁻¹ and 1507.6 cm⁻¹, indicating a high content of aromatic hydrocarbons, which play a crucial role in enhancing the anti-knock properties of gasoline and kerosene, increasing their octane rating. The second sample showed a lower content of aromatic hydrocarbons and a predominance of alkanes, making it more suitable for diesel fuel production, ensuring a high cetane number and improved combustibility. The results obtained are of high practical significance for the petrochemical industry and can be used to improve hydrocarbon mixture processing technologies, as well as enhance the efficiency and environmental sustainability of these processes.